International tourism management - Bhatia, A. K. (New Delhi, India : Sterling Publishers, 2001)
International tourism represents one of the world`s largest industries with nearly 720 million estimated global visitor arrivals at the turn of the present century, which is expected to reach 1.5 billion by the year 2020.This great phenomenon today has become a very complex activity encompassing a wide range og disciplines. The book,"International Tourism Management", tries to examine this complex global phenomenon, exploring its various concepts in their different manifestations.The book offers comprehensive information on various concepts, methods and framework giving a systematic overview of the subject on a global basis.Key elements of the book include:nature and components of the tourism industry; and communication; economic dimensions and international cooperation. The book will be of value to students pursuing tourism studies at different levels,particularly as part of various courses in tourism studies at professional training institutes and colleges affiliated to both Indian and foreign Universities. The text of the book will enable the students, who are to form the future resource of the travel and tourism business, to face the increasingly competative world where they intend to pursue their careers.The book should also be of value to teachers and professionals in the tourism/travel industry, as well as to those seeking opportunities for professional development.
1. Historical Development -- 2. Travel Motivations -- 3. Nature and Components of Tourism Industry -- 4. Travel and Tourism Statistics -- 5. The Role of the State in Tourism -- 6. Marketing Concepts and Strategies in Tourism -- 7. Marketing Communications -- 8. Travel Retailing -- 9. Business Tourism -- 10. Travel Industry Fairs -- 11. Information Technology in Tourism -- 12. International Tourism Organizations -- 13. Tourism Planning and Development -- 14. Accommodation Industry -- 15. Tourist Transport -- 16. Economic Dimensions of Tourism.
Includes bibliographical references and index.
Keywords: TOURISM MANAGEMENT